2014
DOI: 10.1175/jcli-d-13-00412.1
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Processes Contributing to Interannual Halosteric and Thermosteric Sea Level Variability

Abstract: On interannual time scales, regional sea level variability is largely determined by changes in the steric component. The relation between the thermosteric and halosteric components is studied by separating the components into contributions from the mixed layer and, below the mixed layer, into the part that is related to isopycnal motion and that contributes to the steric sea level and the inactive part related to changes of spiciness. The decomposition provides a simple diagnostic to detect and understand phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…While the null hypothesis is of broad value as a qualitative first order depiction, quantitative analyses of interannual fluctuations in f q require taking into account all of the terms shown in Fig. 18 (see also Köhl, 2014).…”
Section: A Variance Ratiomentioning
confidence: 99%
“…While the null hypothesis is of broad value as a qualitative first order depiction, quantitative analyses of interannual fluctuations in f q require taking into account all of the terms shown in Fig. 18 (see also Köhl, 2014).…”
Section: A Variance Ratiomentioning
confidence: 99%
“…Ocean density (steric) changes reflect surface fluxes or redistribution of heat and salt, while mass changes can be driven either by addition of freshwater or mass redistribution (e.g., by wind stress). On decadal timescales, gravimetric data, in conjunction with altimetry, allow the separation of steric and mass components [49][50][51]; in situ ocean observations facilitate further partitioning into halosteric and thermosteric components that can be traced back to their origin in surface fluxes and/or redistribution [38,52,53]. Recent studies have shown that satellite-era changes are dominated by the baroclinic response to wind stress and buoyancy fluxes, with mass redistribution and barotropic adjustment influencing sea level at larger spatial scales [50,51].…”
Section: Ocean-atmosphere Dynamicsmentioning
confidence: 99%
“…Thermosteric redistribution-driven by wind stress curl and isopycnal displacement-underlies sealevel variability over most of the world's oceans. Halosteric changes-driven by redistribution and external sources (melting of sea and land ice)-contribute substantially in polar regions [52][53][54].…”
Section: Ocean-atmosphere Dynamicsmentioning
confidence: 99%
“…Second, we consider total column heat content ( H tot ), the volume of which is generally dominated by the ocean interior that is away from direct atmospheric influences. H tot is particularly relevant for interannual changes in steric sea level in the low latitudes and midlatitudes that are dominated by the thermosteric response to wind‐stress variations [ Köhl , ; Forget and Ponte , ; Stammer et al ., ; Roberts et al ., ].…”
Section: Introductionmentioning
confidence: 99%